Eklesiologi Ekaristik: Reorientasi Eklesiologi Evangelikal dalam Terang Pemikiran Alexander Schmemann - Augustan, Hansel (Veritas : Jurnal Teologi dan Pelayanan, 2023)
Evangelicals are known for their unique ecclesiology. Evangelicalism believes that the true church is a spiritual fellowship of saved believers. This perspective in fact leads to the consequence that the invisible church is upheld and the visible church becomes soteriologically irrelevant. As a result, the visible church only ends up as a commodity marketed to attract converts. If evangelicals are faithful to the gospel, then the concept of the church must be taken seriously, not just perceived functionally. For this reason, I propose the construction of a eucharistic ecclesiology through the framework of Alexander Schmemann’s thoughts on the liturgy, the Eucharist, and the church in providing an alternative to seeing ecclesiology from liturgical studies. I shall integrate Schmemann’s thinking with the idea that a “worshipping community essentially formed the church.” My claim is: that a eucharistic ecclesiology rooted in the practice of the eucharistic liturgy can be a solid ecclesiological basis for evangelicals, especially in affirming the ontology of the church. I hope that the construction of eucharistic ecclesiology can contribute to revitalizing evangelical ecclesiology.